ESTUDIO DE IMPACTO AMBIENTAL DEL PROYECTO TROCHA CARROZABLE CARRIZAL - MONTE RICO DISTRITOS JEPELACIO - SAN MARTÍN ALAO, REGION SAN MARTÍN PROPUESTA METODOLOGIA - Rodas Hernandez, luis Isidoro (2006)
Environmental Impact Study (EIA), allows documenting the entire analysis of Environmental impacts of a given action as the different alternatives for its implementation, mitigation and / or compensation measures, and growth, monitoring and control plans. The purpose of the Environmental Impact Study is to ensure the sustainable development of the project, inducing its economic and social growth by the orientation towards the control of environmental pollution, and this document should be considered as the initial part in the planning and development of the .ect The construction and / or improvement of roads in our country is very important because it allows the interconnection of towns and commercial exchange, which is an important factor for local, regional and country economic development, but is itself a source of Threatening to the environment, of not taking adequate measures to correct, mitigate, eliminate or minimize the negative impacts that may be generated. Facing this need is that we chose to work a Methodological Proposal for Environmental Impact Study as a corrective and minimizing of impacts that is generated during the construction and operation of the same. The geographical area where the Carrozable Trocha will be executed, is located between the districts of Jepelacio and San Martín de Alao, Provinces of Moyobamba and El Dorado in the Department of San Martín. The stretch to be built between the Carrizal Village Center and the Monte Rico Village Alto Sisa, has a length of 25Km. The same one that forms part of the route Moyobamba - Jepelacio - New San Miguel, important way that constitutes the direct access to the Road Fernando Belaunde Terry in the Province of Moyobamba. The applied methodology, in the research work has three stages defined: Preliminary Cabinet Stage This stage began with the compilation of existing thematic information, was designed and determined the number of surveys. Likewise, the analysis of the relationships between the engineering activities of the Project and the Environment was carried out, with the purpose of determining the level of study, which in this case is executed at the Semi-detailed level. In the Field Stage, they began with the recognition of the study area, and then the techniques and procedures already designed were sicaron with the purpose of generating and collecting information to be processed and analyzed for our purposes. All this information proves to be very important for the Elaboration of the Environmental Baseline, which describes the current characteristics of the physical, biological and anthropic environment of the area of ​​influence of the project. In addition, the Political and Citizen Participation was achieved, which has a double direction: on the one hand to inform the population evolved in the area of ​​influence of the trocha Carrozable the aspects of the project that will generate social and environmental impacts, and on the other hand, the full participation of It is villagers who have expressed their concerns and conformities that have been taken into account; The commitments they assume in favor of the environment. In the final stage of the Cabinet, the systematization, analysis, evaluation and interpretation of all the information collected in previous stages was carried out; The environmental impacts were defined according to the occurrence and magnitude that the project execution can generate, as well as the final thematic maps were prepared. At the same time, the Environmental Management Plan (Mitigation, Environmental Education, Monitoring, Contingencies, Abandonment, Environmental Cost) was structured in the same stage that is established within the framework of laws and normative agents.